2017
DOI: 10.1111/rec.12629
|View full text |Cite
|
Sign up to set email alerts
|

Comparing seed removal rates in actively and passively restored tropical moist forests

Abstract: High rates of seed removal can impede forest recovery, but tropical seed removal studies are few and mainly from the neotropics. Little is known about the comparative influences of active restoration (i.e. planting) and passive restoration (i.e. protection of natural regrowth) on seed removal. We conducted an evaluation of seed removal in grasslands, natural forests (tropical moist semideciduous forest), and actively (21‐, 17‐, 16‐, 11‐, 8‐, and 6‐year‐old) and passively (21‐year‐old) restored forests in Kibal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…For example, even if forest and bracken started with the same seed number, maintaining the same 3‐day rate of seed removal over a 30‐day interval would result in more than 800 times more seeds in the forest. Other studies have also reported a significantly higher rate of seed removal in treeless areas than in nearby forest (in Indonesia, Blackham & Corlett, ; in Netherlands, den Ouden, ; and in Madagascar, Razafindratsima, ) although such patterns are not universal, for example, grassland versus forest in Kibale Forest in Uganda (Ssekuubwa, Loe, Sheil, Tweheyo, & Moe, in press).…”
Section: Discussionmentioning
confidence: 96%
“…For example, even if forest and bracken started with the same seed number, maintaining the same 3‐day rate of seed removal over a 30‐day interval would result in more than 800 times more seeds in the forest. Other studies have also reported a significantly higher rate of seed removal in treeless areas than in nearby forest (in Indonesia, Blackham & Corlett, ; in Netherlands, den Ouden, ; and in Madagascar, Razafindratsima, ) although such patterns are not universal, for example, grassland versus forest in Kibale Forest in Uganda (Ssekuubwa, Loe, Sheil, Tweheyo, & Moe, in press).…”
Section: Discussionmentioning
confidence: 96%
“…Ssekuubwa et al (2018) showed that seed removal in our study sites was not influenced by restoration age. If we interpret seed removal as secondary seed dispersal (Vander Wall et al 2005), then the seed removal rates reported by Ssekuubwa et al (2018) could indicate a uniform availability of seeds for germination among restoration sites of different ages. Thus, seedling colonization in our sites may be more microsite-limited than seed-limited.…”
Section: Effect Of Sampling Year Restoration Age and Distance From mentioning
confidence: 49%
“…Seed predation impedes seedling colonization (Holl et al 2000) while dispersal improves colonization of seedlings (García et al 2005). More recently, Ssekuubwa et al (2018) showed that the rate of removal of seeds of woody species in our sites was higher for passively than actively restored forests. If the seed removal guild in our sites is composed of more seed dispersers than predators, then possibly more seeds reach suitable microhabitats for germination, and seedling predation is reduced, which increases colonization in passively restored forests.…”
Section: Effect Of Restoration Methods On Species Diversity Richnessmentioning
confidence: 58%
See 1 more Smart Citation
“…Com a reestruturação da comunidade animal, processos ecológicos tendem a ressurgir e se intensificar. A remoção de sementes é um processo ecológico importante para avaliar a recuperação de ecossistemas funcionais e pode afetar a composição de espécies vegetais que se estabelecem nos locais perturbados e em restauração (Queiroz et al 2021;Ssekuubwa et al 2018). Entre os insetos, os principais agentes de remoção são as formigas e estas podendo atuar como predadores ou dispersores (Vander Wall et al 2005).…”
Section: Introductionunclassified